Filosofía y Educación en América Latina (2022)
This text makes an introduction and a brief presentation of the different contributions to the dossier. Specifically, the paper identifies the different meanings and perspectives in which philosophical reflections on the different aspects of education in Latin America have been raised, shows some thematic lines of the reflections, relates these reflections with some approaches of Latin American philosophy, justifies the importance of continuing and promoting philosophical work in this broad field of philosophical reflection, and poses some challenges for future reflections. Finally, the articles that are part of the dossier are presented and commented.